Lietuvos integrali bibliotekų informacijos sistema: istorija ir plėtros perspektyva - Bulavas, Vladas; Varnienė, Regina (Knygotyra, 2003)
The article examines the main stages of the creation and implementation of Lithuanian Integrated Library Information System (LIBIS) Project, assesses the achieved results and presents the guidelines of its future development.In 1994, on the initiative and with the efforts of the National Library of Lithuania (NLL) a Concept of LIBIS, setting forth the principal objectives and aims of the establishment of the Integrated Information Library System, its organizational and functional structure, was worked out.In 1996, the realization of the project was begun under approved by the Government Program. The projecting, programming and implementing of LIBIS were put on Sintagma Sistemos IT Company together with the NLL. The latter carried out all the organizational and financial responsibility for implementation and maintenance of LIBIS. On 1 June 1998 the first LIBIS Subsystem - Union Catalogue (UC) of Lithuanian research libraries - was launched with 50 libraries participating in it.The following Subsystems are recently operating within the LIBIS:• Union Catalogue, providing access to holdings information of documents located in Lithuanian libraries;• National Bibliographic Data Bank, providing access to information on Lithuanian and related to Lithuania documents;• Readers Services and Circulation, providing access to the LIBIS libraries using Common Readers database and uniform readers ticket;• Archive of Electronic Resources, providing harvesting and archiving of ER, and access to ER;• Analytical Bibliography, providing access to bibliographic information on component parts of Lithuanian press and serials, compiled by the LIBIS libraries within the National Bibliographic Data Bank.The main LIBIS Software Modules were developed by Sintagma Sistemos IT Company and operating within LIBIS libraries: Acquisition, Cataloguing, Serials Control, OPAC, Publishing, Interlibrary Loan, Retro Conversion, a.o. LIBIS SW supports UNICODE standard ISO-10646 for coded information and guarantees the support of multilingual scripts. WWW and Z39.50 modules are operating for search and retrieval of bibliographic information.The LIBIS is implemented up to the year 2003 in 48 libraries, including NLL and 3 research libraries, Library for the Blinds, 5 County and 34 town and district municipal Public libraries. In the year 2003 the System will be extended to 13 municipal Public libraries. From 1997 to 2002 over 7.5 million Litas for the realization of LIBIS were received from the State budget and consumed (excluding the money spent on creation of the separated from the LIBIS Academic Libraries network) out of the total of 20.7 million Litas allocated to the LIBIS program.New LIBIS functions are associated with the formation of huge information bulks, ensuring their accessibility and long-term preservation. The tasks to be solved primarily are the extension of LIBIS to all the public and school libraries, further creation and development of local and national databases, including the UC, the National Bibliographic Data Bank, full-text documents, electronic resources, provision of access to data. In addition, the new functions and wider scale of LIBIS implementation will call for creating new legal and normative documents, to form system management and administration groups.Realizing the new functions in libraries, it is necessary to improve already operating library systems by inventing and introducing more updated technologies, more optimal processes and structures. The accomplishment of the Lithuanian Library Modernization Program, in which library computerization requirements are considered as one of predominant objectives, is of great consequence to further LIBIS development and advancement of libraries in Lithuania.